Simai Erdős József, a negyedik rektor - Csohány, János (Gerundium, 2012)
József Simai Erdős, the Fourth Rector. The fourth rector of the University of Debrecen was József Erdős, who was born in Szatmárnémeti and who pursued his studies in Debrecen and Vienna. For a short time after 1888 he served as minister at the Theological Academy of Debrecen’s Protestant College, then, from 1914, at the Faculty of Theology of the newly-established university he was professor of New Testament exegesis. When, as dictated by the principle of rotation, it was again the Faculty of Theology’s turn to delegate a new Rector, in the academic year of 1917/18 he became the fourth Rector of the University. In 1908 be received a title of Hungarian nobility, and in 1946 the silver-headed scholar was awarded the title of Doctor honoris causa. He carried on extensive work in the history of religion (The General Outlines of the Life and Reformist Activity of Ulrick Zwingli; Theology at the University; The Basic Principles of the Statecraft of Apostle Paul, etc.). He translated and published the Catechism of Heidelberg and the Second Helvetian Creed.